Analisis DMAIC Faktor Penyebab Selisih Screw Di Gudang Sparepart PT. MI - Esther Barbara; Desrina Yusi Irawati (Industrial & System Engineering Journals (ISEJOU), 2022)
Discrepancy is the difference in the number of stock spare parts between the actual number and the amount of stock in the system. PT. MI experienced discrepancy problems, especially in the spare part warehouse. The purpose of this study is to determine the factors causing the difference in the number of goods in the warehouse between the physical and the system and provide solutions in the form of efforts to minimize the data discrepancy. The research method uses DMAIC (Define, Measure, Analyze, Improve and Control) with fishbone diagram analysis techniques. From the measure stage with the p control chart, it is known that there are still many that are outside the UCL and LCL limits. In the analysis stage, use a fishbone diagram to analyze the causes and effects of the problem. From the results of the analysis there are 3 factors that influence the problem, namely the human factor, methods, and work environment. At the improve stage, several attempts are given to the problems that have been analyzed.